Exploring the Influence: A Bibliometric Analysis of Social Media Marketing in the Digital Era - Sudirjo, Frans; Praja, Selvia Junita; Syamsu Rijal (West Science Interdisciplinary Studies, 2023)
This study presents a bibliometric analysis of the term "social media marketing" to explore the growing trends, key contributors, and thematic focus in the academic literature. Social media marketing represents the integration of social media utilization practices and principles into marketing strategies and activities, highlighting the growing importance of technological developments to economic practices in the use of social media. This research examined 980 articles with themes related to marketing management. In the context of this study, we concluded that marketing management articles were classified into twelve clusters. Marketing management research trends related to social media are of great interest to research on the marketing side. There are several topics that frequently appear in publications, such as the social media marketing perspective of one variable against another.